STUDY OF THE EFFECT OF METHIONINE HYPERHOMOCYSTEINEMIA AND ITS CORRECTION WITH CHOLINE AND VITAMIN D ON THE CONDITION OF THE PERIODONTIUM, SMALL INTESTINE, AND LIVER OF RATS - Oleh Kutelmakh; Yulia Chumakova; Lina Kovalchuk; Yulia Odnorih; Olexandra Kutelmakh; Anastasiya Spodaruk (Acta Medica Leopoliensia)
In recent years, there have been reports of a clinical relationship between periodontitis, intestinal and liver diseases of the human body, the so-called "oral-intestinal-hepatic axis", although the causal mechanism of such an "association" is still unclear.